2003
DOI: 10.1074/jbc.m303242200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of Dehydroepiandrosterone to the N Terminus of the Microtubule-associated Protein MAP2

Abstract: The effect of neurosteroids is mediated through their membrane or nuclear receptors. However, no dehydroepiandrosterone (DHEA)-specific receptors have been evidenced so far in the brain. In this paper, we showed by isothermal titration calorimetry that the DHEA specifically binds to the dendritic brain microtubule-associated protein MAP2C with an association constant of 2.7 ؋ 10 7 M ؊1 and at a molar ratio of 1:1. By partial tryptic digestions and mass spectrometry analysis, we found that the binding involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…The location of the PREG-binding site on MAP2 isoforms is not known, although preliminary experiments performed with recombinant MAP2C have indicated that this short isoform also binds PREG (E. Plassart-Schiess, V.F.-L., and E.-E.B., unpublished work). Another steroid, dehydroepiandrosterone, has been found to bind recombinant MAP2C (19), although no function was assigned to this binding. However, MAP2 purified from rat brain poorly binds dehydroepiandrosterone, a likely consequence of posttranslational modifications (6).…”
Section: Discussionmentioning
confidence: 99%
“…The location of the PREG-binding site on MAP2 isoforms is not known, although preliminary experiments performed with recombinant MAP2C have indicated that this short isoform also binds PREG (E. Plassart-Schiess, V.F.-L., and E.-E.B., unpublished work). Another steroid, dehydroepiandrosterone, has been found to bind recombinant MAP2C (19), although no function was assigned to this binding. However, MAP2 purified from rat brain poorly binds dehydroepiandrosterone, a likely consequence of posttranslational modifications (6).…”
Section: Discussionmentioning
confidence: 99%
“…Swapped loop sequences of a set of C-type lectin proteins and prion protein were selected from the Protein Data Bank and aligned with the lithostathine sequence. Homology modeling of the lithostathine dimer was performed largely according to the principles outlined by Greer (16) and as previously described in detail (17), using the software modules InsightII, Homology, and Discover from Accelrys (San Diego, CA) and a Silicon Graphics O 2 work station (SGI, Mountain View, CA). The model of the lithostathine dimer connected by a swapped loop was built from the crystal Protein Data Bank structure of flavocetin-A (1C3A; see Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The binding domain of HWMMAP2 to PREG has not been characterized yet. The LWMMAP2 isoform, MAP2c, was identified as the first brain specific receptor for DHEA [Laurine et al, 2003]. The N-terminal region of MAP2c mediates its binding to DHEA.…”
Section: Receptors For Neurosteroidsmentioning
confidence: 99%
“…MAP2c shows sequence homologies with 17b-hydroxysteroid dehydrogenase 1, an enzyme required for estrogen synthesis. Based on these sequence homologies, the binding of DHEA to MAP2c was modeled [Laurine et al, 2003]. The binding of DHEA to MAP2c would involve hydrophobic residues that would form a hydrophobic pocket with highly specific hydrogen bonds that orient DHEA into the pocket.…”
Section: Receptors For Neurosteroidsmentioning
confidence: 99%